Role of Computational Tools in Structural Analysis and Design - Santosh Kumar, Gottapu (International Journal of Psychosocial Rehabilitation, 2020)
The rapid advancement of computational tools has revolutionized the field of structural analysis and design, offering new possibilities and efficiencies beyond traditional methodologies. This research explores the pivotal role that these tools play in shaping modern engineering practices. The paper begins with a historical context, highlighting the evolution of structural analysis and design and the limitations of conventional approaches. A comprehensive literature review establishes the foundation for understanding the development and integration of computational tools in structural engineering. The methodology section details the specific tools and techniques employed in the research, emphasizing their relevance and effectiveness. The paper delves into the importance of computational tools, discussing their advantages over traditional methods and showcasing real-world applications through insightful case studies. Additionally, it addresses challenges and limitations, offering a nuanced perspective on the current state of the field. The discussion extends to recent innovations and emerging trends, providing a forward-looking view into the future of computational tools in structural engineering. The paper concludes with a summary of key findings and recommendations for practitioners, researchers, and policymakers. By examining the past, present, and potential future of computational tools in structural analysis and design, this research contributes to the ongoing dialogue surrounding the optimization and evolution of engineering practices in the digital age.